Effect of different warm-up procedures on subsequent swim and overall sprint distance triathlon performance - Binnie, M. J.; Landres, G.; Peeling, P. (The Journal of Strength and Conditioning Research, 2012)
This study investigated the effect of 3 warm-up procedures on subsequent swimming and overall triathlon performance. Seven moderately trained, amateur triathletes completed 4 separate testing sessions comprising 1 swimming time trial (STT) and 3 sprint distance triathlons (SDT). Before each SDT, the athletes completed 1 of three 10-minute warm-up protocols including (a) a swim-only warm-up (SWU), (b) a run-swim warm-up (RSWU), and (c) a control trial of no warm-up (NWU). Each subsequent SDT included a 750-m swim, a 500-kJ (~20 km) ergometer cycle and a 5-km treadmill run, which the athletes performed at their perceived race intensity. Blood lactate, ratings of perceived exertion, core temperature, and heart rate were recorded over the course of each SDT, along with the measurement of swim speed, swim stroke rate, and swim stroke length. There were no significant differences in individual discipline split times or overall triathlon times between the NWU, SWU, and RSWU trials (p > 0.05). Furthermore, no difference existed between trials for any of the swimming variables measured (p > 0.05) nor did they significantly differ from the preliminary STT (p > 0.05). The findings of this study suggest that warming up before an SDT provides no additional benefit to subsequent swimming or overall triathlon performance.